Corrosion Behaviours of High Strength TMT Steel Bars for Reinforcing Cement Concrete Structures. (2015) - Islam, Md. Aminul
Abstract: Steel has been used for many decades in structural applications because of its good combination of mechanical properties. As per recent concept to reduce steel consumption in reinforced cement concrete (RCC) structures, designers recommend high strength steel bars. There are various routes for their production such as microalloying, thermomechanical treatment, cold working, etc. For steel bars of thermomechanical treatment (TMT) route, some designers believe these steel bars to be more sensitive to corrosive environment. To verify this, corrosion behaviours of high strength steel bars of 500W (weldable steel bar of yield strength 500 MPa) grade of two different local industries have been studied in fresh water and sea water, which were compared with weldable low strength (yield strength 300 MPa) bars of the same companies. Experimental results revealed that addition of small amount of alloying elements such as Cr, Ni and Cu improves the corrosion resistance of the steel bars in all test mediums; however, strength levels have no influence the corrosion rate. A relation has also been found between the severity of corrosion damage and the degree of tensile property degradation.